X-ray structural studies of quinone reductase 2 nanomolar range inhibitors - Pegan, Scott D (Wiley Subscription Services, Inc., A Wiley Company, 2011)
Quinone reductase 2 (QR2) is one of two members comprising the mammalian quinone reductase family of enzymes responsible for performing FAD mediated reductions of quinone substrates. In contrast to quinone reductase 1 (QR1) which uses NAD(P)H as its co-substrate, QR2 utilizes a rare group of hydride donors, N-methyl or N-ribosyl nicotinamide. Several studies have linked QR2 to the generation of quinone free radicals, several neuronal degenerative diseases, and cancer. QR2 has been also identified as the third melatonin receptor (MT3) through in cellulo and in vitro inhibition of QR2 by traditional MT3 ligands, and through recent X-ray structures of human QR2 (hQR2) in complex with melatonin and 2-iodomelatonin. Several MT3 specific ligands have been developed that exhibit both potent in cellulo inhibition of hQR2 nanomolar, affinity for MT3. The potency of these ligands suggest their use as molecular probes for hQR2. However, no definitive correlation between traditionally obtained MT3 ligand affinity and hQR2 inhibition exists limiting our understanding of how these ligands are accommodated in the hQR2 active site. To obtain a clearer relationship between the structures of developed MT3 ligands and their inhibitory properties, in cellulo and in vitro IC(50) values were determined for a representative set of MT3 ligands (MCA-NAT, 2-I-MCANAT, prazosin, S26695, S32797, and S29434). Furthermore, X-ray structures for each of these ligands in complex with hQR2 were determined allowing for a structural evaluation of the binding modes of these ligands in relation to the potency of MT3 ligands.